2009
DOI: 10.1161/circresaha.108.188698
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Basis for Electrophysiological Heterogeneity in the Ventricular and Outflow Tract Myocardium As a Substrate for Life-Threatening Ventricular Arrhythmias

Abstract: Abstract-Reentry is the main mechanism of life-threatening ventricular arrhythmias, including ventricular fibrillation and tachycardia. Its occurrence depends on the simultaneous presence of an arrhythmogenic substrate (a preexisting condition) and a "trigger," and is favored by electrophysiological heterogeneities. In the adult heart, electrophysiological heterogeneities of the ventricle exist along the apicobasal, left-right, and transmural axes. Also, conduction is preferentially slowed in the right ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 173 publications
2
105
0
3
Order By: Relevance
“…Each cell type (e.g., pacemaker cell, atrioventricular nodal cell, Purkinje fiber, atrial myocyte, ventricular myocyte) is characterized by a distinctive expression pattern of genes encoding a variety of ion channels that determine their specific electrophysiological profile. These electrophysiological properties of the heart develop during embryogenesis and further mature postnatally; accordingly, embryonic and fetal cells do not exhibit the same electrical behavior seen in adult myocytes (21).…”
Section: Do Ips-derived Myocytes Reliably Model the Complexity Of Thementioning
confidence: 97%
“…Each cell type (e.g., pacemaker cell, atrioventricular nodal cell, Purkinje fiber, atrial myocyte, ventricular myocyte) is characterized by a distinctive expression pattern of genes encoding a variety of ion channels that determine their specific electrophysiological profile. These electrophysiological properties of the heart develop during embryogenesis and further mature postnatally; accordingly, embryonic and fetal cells do not exhibit the same electrical behavior seen in adult myocytes (21).…”
Section: Do Ips-derived Myocytes Reliably Model the Complexity Of Thementioning
confidence: 97%
“…9,10 Cardiac myocytes of the RVOT in a normal heart can be arrhythmogenic and the embryonic outflow tract consists of slow conducting tissue. 23 Recently, Nademanee et al demonstrated in patients with BrS that fractionated electrograms were recorded at the epicardial side of the RVOT and that catheter ablation of these electrograms eliminated type 1 ECG and VF. 24 These results may provide strong support for the depolarization theory.…”
Section: Discussionmentioning
confidence: 99%
“…Depolarization theory [15] focuses on conduction slowing in the right ventricular outflow tract (RVOT), leading to ST segment elevation in right precordial leads. Recently, a third hypothesis has been proposed, suggesting that the embryological development of the RV could explain the electrophysiological heterogeneity in the ventricular myocardium, including the RV outflow tract, which could provide the arrhythmogenic substrate [16]. These models are not mutually exclusive, and it is possible that BrS could be a mechanistically heterogeneous disease [17].…”
Section: Molecular Mechanismsmentioning
confidence: 99%